An Empirical Study into Comparing Conventional and Islamic Banks in the UAE - Kapur, Manoj (International Journal of Accounting & Finance Review, 2020)
Banking system constitutes the fundamental pillar of every economy. Banks acts financial intermediaries between sectors that have excess funds and those that are in deficit. Islamic banks operate under Sharia principles of risk sharing and interest prohibition as contrasted with conventional banks that buy capital to pool funds and sell capital to generate interest income or profit. This paper applies banks’ internal factors related to their balance sheet and income statement and using a total of 23 financial ratios pertaining to the internal factors, it attempts to compare and contrast between conventional and Islamic banks. This research explains the structure, operation and management of banks in the UAE coupled with the functioning of Islamic banks. The paper also aims to determine the profitable and efficient banks among the chosen sample. The sample includes 12 banks, equally distributed between Islamic and conventional banks using data between the periods of 2014 - 2018. The sample is broadly categorized based on profitability ratio, efficiency ratio, asset indicator ratio and risk ratios. Correlation and Regression analysis is used to determine a substantial ratio analysis between conventional and Islamic banks. Results from the study reveal indicators of financial characteristics such as profitability ratios, efficiency ratios, asset quality indicators and risk/ risk management ratios. The results clarify that Islamic banks are operationally efficient and profitable because of risks sharing and greater dependency on deposits capital. However, on an overall basis, the ratios indicate conventional banks have higher scores than their counterparts.JEL Classification Codes: F37.